NILAI BUDAYA DALAM ANTOLOGI CERITA RAKYAT ASAL USUL PEMANGKAT - Isytar, Elintara Putri; Priyadi, Antonius Totok; Wartiningsih, Agus (Universitas Tanjungpura, 2022)
This study aims to identify and describe the relationship between humans and God, with themselves, with other humans, with nature, and the implementation of cultural values in learning literature in high school. Cultural values that can be studied in the Anthology of the Origin of Pemangkat Folklore as an effort to appreciate and not folklore. This research was taken from 5 folklores, namely 1) Pemangkat Origin, 2) Batu Ballah Batu Betangkup, 3) Elephant Mountain Trunk to the West, 4) Ocean Guardian Goddess, 5) Sinam Beach Formation. The method used is descriptive method. Data analysis in this study was conducted inductively, thus producing an essential meaning in qualitative research. The approach used is the mimetic approach proposed by Abrams using the sociological literature proposed by Darmono. The data collection technique is a documentary study. The data collection tool used in this research is a document in the form of the work of 5 folk tales contained in the Anthology of Folklore of Origin Pemangkat. The data analysis technique in this study was descriptive qualitative using a sociological approach to literary works. The results of this study can be applied in schools through the cultural values contained in the Anthology of Folklore of Origin Pemangkat and can be taught to students in schools. The results of the analysis of cultural values can be stated as follows. Humans with God, namely believing in the existence of God, believing that sustenance is God's will, and believing in supernatural things. human relationships with themselves, namely emotions, feelings of pity/pity, surrender and patience, mutual understanding, never give up, despair, and strong will. human beings with other humans, namely a sense of humanity, help, respect for others, a sense of responsibility, mutual understanding, tolerance, and compassion. Human relations with nature, namely nature provides food, maintains the beauty of nature, preserves nature, nature provides prey, nature provides human needs, nature provides food, and humans destroy nature. The suggestions given in this study are as follows, the results of this study become a reference for Indonesian language teachers in learning literature in schools. In addition, the results of this study can be a reference for future researchers. Also the results of this study are expected to be a mandate or role model for human life when reading the cultural values that have been found in the Folklore of the Origin of Pemangkat. Keywords: Cultural Values, Anthology, Pemangkat Folklore